Phenotypic description of cardiac findings in a population of Dogue de Bordeaux with an emphasis on atrial fibrillation. (April 2018) - McAulay, G.; Borgeat, K.; Sargent, J.; Mõtsküla, P.; Neves, J.; Dukes-McEwan, J.; Luis Fuentes, V.
Highlights: A retrospective review of Dogue de Bordeaux presenting to the cardiology services of two referral hospitals was performed. Cardiac masses and congenital heart disease, particularly subaortic stenosis, were identified frequently. The frequency of supraventricular arrhythmia, specifically fast persistent atrial fibrillation, was high. Atrial fibrillation was inconsistently associated with structural heart disease or cardiac chamber enlargement. An underlying primary arrhythmic process might be responsible for initiating remodelling in some dogs. Abstract: The aim of this study was to describe the clinical phenotype of Dogue de Bordeaux (DdB) referred for cardiac investigation, with particular reference to the prevalence of atrial fibrillation and associated features. Review of canine medical records of two United Kingdom veterinary referral hospitals identified 64 DdB with available echocardiographic and electrocardiographic (ECG)/Holter data. Atrial fibrillation was documented in 25 (39%) dogs and supraventricular tachycardia was recorded in five (7.8%) dogs. In a subset of 34 dogs, excluding congenital heart disease ( n  = 17), presence of a cardiac mass ( n  = 7) and non-cardiac neoplasia ( n  = 6), 19 (56%) dogs had atrial fibrillation, with a median heart rate of 200 beats per min (bpm) on presentation. Atrial fibrillation was inconsistently associated with cardiac chamber remodelling, but was frequently associated with systolic dysfunction (13/19, 68.4%) and right sided atrial or ventricular dilatation (14/19, 73.7%) in dogs with atrial fibrillation in this subset. No dogs in this subset had right sided atrial or ventricular dilatation in the absence of supraventricular arrhythmia or systolic dysfunction. The absence of structural heart disease in some dogs with supraventricular arrhythmias suggests that an underlying primary arrhythmic process might be responsible for initiating remodelling, although a primary cardiomyopathy cannot be ruled out.